The Greeks West of the Rhone (F). Genesis, Evolution and End of a Greek Area - Ugolini, Daniela (Journal of Greek Archaeology, 2018)
According to ancient texts, all several centuries more recent than the city’s beginning, ancient historians claimed that Agde (Agàthe) was a ‘city of Marseille’, with an uncertain foundation date, while the Hérault river was the border between the Massalian domain and that of the Greek city of Empòrion. The western natives were seen as turned towards Iberia and it was assumed they developed an ‘Ibero-Languedocian civilisation’.